2016
DOI: 10.1371/journal.pone.0166324
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin Treatment Improves Acute Hemodynamic Instability and Reduces Myocardial Damage in Post-Cardiac Arrest Myocardial Dysfunction

Abstract: AimsHemodynamic instability occurs following cardiac arrest and is associated with high mortality during the post-cardiac period. Urocortin is a novel peptide and a member of the corticotrophin-releasing factor family. Urocortin has the potential to improve acute cardiac dysfunction, as well as to reduce the myocardial damage sustained after ischemia reperfusion injury. The effects of urocortin in post-cardiac arrest myocardial dysfunction remain unclear.Methods and ResultsWe developed a preclinical cardiac ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Microscopically, we found that Sal B treatment attenuated myocytolysis and inhibited cardiomyocyte apoptosis with preserved mitochondrial morphology in this model. It is noteworthy that whether apoptosis is one of the main mechanisms of postresuscitation myocardial dysfunction remains controversial [ 36 39 ]. The experimental animals and the inducers of CA could be driving these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, we found that Sal B treatment attenuated myocytolysis and inhibited cardiomyocyte apoptosis with preserved mitochondrial morphology in this model. It is noteworthy that whether apoptosis is one of the main mechanisms of postresuscitation myocardial dysfunction remains controversial [ 36 39 ]. The experimental animals and the inducers of CA could be driving these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological and histological results of the brains were examined by hematoxylin and eosin staining. Healthy neurons had oval nuclei with prominent nucleoli and a lack of eosinophilic cytoplasm [ 17 , 18 ]. The cornu amonis (CA1, CA2, CA3) in the hippocampus of each brain was selected for brain injury studies.…”
Section: Methodsmentioning
confidence: 99%
“…There are data that urocortin-2 can improve acute hemodynamic instability, reduce myocardial damage in post-cardiac arrest myocardial dysfunction in rats. 72 It increased phosphorylation of Akt, ERK and STAT-3.…”
Section: The Cardioprotective Effect Of Crf and Urocortinsmentioning
confidence: 97%